ANALISIS TINDAK TUTUR DALAM BUKU BACAAN â€œLEGENDA CERITA RAKYAT NUSANTARAâ€ - Pratiwi, Asti Nur; Nugraheni, Aninditya Sri (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2020)
Abstract                This mini research aims to: (1) explain and describe speech acts such as what is used in writing the book "Legenda Cerita Rakyat Nusantara", (2) explain the meaning of speech acts contained in the reading book.                This type of research is descriptive research. Then the data analysis technique uses qualitative descriptive techniques and pragmatic analysis. Data analysis was carried out through several stages, namely the stages of reading, identifying, categorizing, describing, and concluding. Data sourced from the book reading "Legenda Cerita Rakyat Nusantara" by Cahaya Fadilah published by Pustaka Anak Bangsa.                The results obtained from this mini research can be summarized as follows: (1) speech acts used in reading books "Legenda Cerita Rakyat Nusantara" are acts of locution, illocution, and perlocution, (2) the meaning of speech acts contained in reading books these include to ask / pray, declare, decide, rule, and invite. Keywords: speech acts, readings books